Comparison of force measures between start position, transition phase, and midthigh pull with weightlifting performance during Israel national competition - Ben-Zeev, T.; Sadres, E.; Hoffman, J. R. (The Journal of Strength and Conditioning Research, 2023)
This study compared the relationship between peak force (PKF) and rate of force development (RFD) at isometric start position pull (ISPP), isometric transition position pull (ITPP), and isometric midthigh pull (IMTP) with the snatch (SN), clean and jerk (C&J), and total score (TOT) in 30 national and international Israeli weightlifters (18 men and 12 women). All measures were collected either 1 week before or 1 week after the Israel weightlifting championship. A significant correlation was observed between peak force at all pull positions and performance in the SN, C&J, and TOT for men, women, and both sexes combined (p < 0.001). The correlations were all very strong (e.g., r values all above 0.90) for both ISPP and ITPP, and all weightlifting performance variables, whereas the correlation between IMTP and weightlifting performance ranged from moderate (r = 0.69) to strong (r = 0.89). In addition, significant differences were observed between the correlation coefficient value in ISPP and ITPP with the TOT score compared with the correlations observed in IMTP (z = 0.7, p = 0.046, and z = 1.7, p = 0.049, respectively). Significant differences were also observed in the women group for ISPP for the SN and TOT score compared with the correlation in IMTP (z = 1.72, p = 0.043, and z = 1.75, p = 0.040, respectively). Rate of force development at 250 milliseconds significantly (p values <0.05) correlated with the SN, C&J, and TOT in women (r's = 0.65, 0.68, and 0.67, respectively), and when both sexes were combined (r's = 0.59, 0.61, and 0.60, respectively), but not for the men. Results of this investigation indicated the importance of isometric force capabilities at ISPP and ITPP for weightlifting performance.